Youth acceptance towards the Sabah Sarawak Keluar Malaysia (SSKM) campaign in Kota Kinabalu, Sabah / Merelene Dungkung and Serhan Salim - Dungkung, Merelene; Salim, Serhan (2016)
The campaign of SSKM has been going actively in Sabah and they try to promote a view that Sabah should secede from the Federation of Malaysia. This study was constructed to determine youth acceptance towards Sabah Sarawak Keluar Malaysia campaign in Kota Kinabalu, Sabah. This paper also investigates the relationships of the influencing factors which are social media, family, friends, civil society, knowledge of youth and youth acceptance towards SSKM campaign. There are 140 respondents for this study that consist of youth living in Kota Kinabalu area. Questionnaires were distributed to respondents through random sampling technique. The findings reveal that the youth acceptance towards SSKM campaign in Kota Kinabalu is on average. The outcomes also shows that there is a relationship of the influencing factors and youth acceptance towards SSKM campaign, whereas the influencing factors like knowledge of youth regarding the issues raises by SSKM and information about SSKM gives influence on the youth acceptance towards SSKM campaign.